Investeringsalternativ för gårdsbaserad bioanläggning vid SLU - Alonso, Marcos (SLU/Dept. of Economics, 2010)
A Biogas plant in SLU’s (Swedish University of Agricultural Sciences) management sustains to behave in con-nection with the new animal stables at Lövsta. There will primarily manure from stables that rot to biogas. The biogas plant will also have the capacity that rot others substrates that can arise in the farm operation. The aim with the biogas plant is to produce non fossil electrical and gas heat for own customs, to reduce smell impact from stables and to make possible different types of research investments within the area.